Nostalgia and Self-Authentication in Lawrence Vambe's An Ill-fated People: Zimbabwe before and after Rhodes. Issue 2 (2nd July 2016) - Nyanda, Josiah
Abstract : The article discusses nostalgia as a purposeful narrative strategy adopted in order to authenticate Lawrence Vambe's narrative in a colonial context. I argue that nostalgia for Vambe is not just a narrative technique, but a practice in self-authentication and marketing. Focusing on Vambe's use of 'selective nostalgia', I offer a reading of his memoir as an anti-colonial personal discourse opposed to the dominance of imperial narratives and colonialism in Africa's socio-political, economic and cultural realms. This approach reveals the utilitarian nature of the memoir, and speaks to the intentionality and functionality of text.